On The Possible Leakage of ET-RR1 Liquid Waste Tank: Hydrological and Migration Modes Studies - N. S. Mahmoud; S. T. EL-Hemamy (The Scientific World Journal)
The first Egyptian (ET-RR1) research reactor has been in operation since 1961 at the Egyptian Atomic Energy Authority (EAEA) Inshas site. Therefore, at present, it faces a serious problem due to aging equipment, especially those directly in contact with the environment such as the underground settling tanks of nuclear and radioactive waste. The possible leakage of radionuclides from these aging tanks and their migration to the aquifer was studied using instantaneous release.This study was done based on the geological and hydrological characteristics of the site, which were obtained from the hydrogeological data of 25 wells previously drilled at the site of the reactor[1]. These data were used to calculate the trend of water levels, hydraulic gradient, and formulation of water table maps from 1993–2002. This information was utilized to determine water velocity in the unsaturated zone.Radionuclides released from the settling tank to the aquifer were screened according to the radionuclides that have high migration ability and high activity. The amount of fission and activation products of the burned fuels that contaminated the water content of the reactor pool were considered as 10% of the original spent fuel. The radionuclides considered in this case were H-3, Sr-90, Zr-93, Tc-99, Cd-113, Cs-135, Cs-137, Sm-151, Pu-238, Pu-240, Pu-241, and Am-241.The instantaneous release was analyzed by theoretical calculations, taking into consideration the migration mechanism of the various radionuclides through the soil space between the tank bottom and the aquifer. The migration mechanism through the unsaturated zone was considered depending on soil type, thickness of the unsaturated zone, water velocity, and other factors that are specific for each radionuclide, namely retardation factor, which is the function of the specific distribution coefficient of each radionuclide. This was considered collectively as delay time. Meanwhile, the mechanism of radionuclide migration during their passage in the water body of the aquifer was the main focus of this study.The degree of water pollution in the aquifer at a point of contact with the main water body of Ismailia Canal 1000 m from the reactor site was assessed for the instantaneous release by comparing the results obtained with the regulations of the standard limit of radionuclides in drinking water[2,3].